2017
DOI: 10.1177/0961203317735187
|View full text |Cite
|
Sign up to set email alerts
|

Low copy numbers of complement C4 and homozygous deficiency of C4A may predispose to severe disease and earlier disease onset in patients with systemic lupus erythematosus

Abstract: ObjectivesLow copy numbers and deletion of complement C4 genes are potent risk factors for systemic lupus erythematosus (SLE). However, it is not known whether this genetic association affects the clinical outcome. We investigated C4 copy number variation and its relationship to clinical and serological features in a Northern European lupus cohort.MethodsWe genotyped the C4 gene locus using polymerase chain reaction (PCR)-based TaqMan assays in 169 patients with SLE classified according to the 1997 revised Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…C1q AR SLE, AGS [18][19][20][21][22][23][24] C1r/C1s AD [7,25,26] C2 AR [27] C4 AR [28][29][30][31][32] Type…”
Section: Complement Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…C1q AR SLE, AGS [18][19][20][21][22][23][24] C1r/C1s AD [7,25,26] C2 AR [27] C4 AR [28][29][30][31][32] Type…”
Section: Complement Pathwaymentioning
confidence: 99%
“…In contrast, the copy number variation (CNV) of C4 genes (C4A and C4B), which ranges from two to eight copies, is recognized as a crucial factor in prediction of the risk for juvenile-onset SLE [28,29]. Recent population studies consistently showed that the higher the copy number of C4 genes, the lower the risk of non-mendelian SLE, and vice versa [29][30][31][32]. High numbers of auto-reactive B cells, glomerulonephritis and increased levels of autoantibodies were detected in mice with defective C4 genes [116].…”
Section: Complement Pathwaymentioning
confidence: 99%
“…Rare cases of severe, early-onset SLE can involve complete deficiency of a complement component (C4, C2, or C1Q) 32,33 , and one of the strongest common-variant associations in SLE maps to ITGAM, which encodes a receptor for C3, the downstream 80 effector of C4 21,34 . Though total C4 gene copy number associates with SLE risk [35][36][37] , this association is thought to arise from linkage disequilibrium (LD) with nearby HLA alleles 38 , which have been the focus of fine-mapping analyses [6][7][8][9][10][11]21 .…”
mentioning
confidence: 99%
“…Characteristically, lupus in these patients develops at an early age and many have severe cutaneous involvement ( 16 ). Extrapolating from these observations, it has also been noted that SLE patients as a whole are more likely to have lower copy numbers of C4A and C4B genes as compared to healthy populations, and this is especially striking in earlier onset disease ( 17 , 18 ).…”
Section: Monogenic Lupusmentioning
confidence: 92%